2020
DOI: 10.1055/s-0040-1710558
|View full text |Cite
|
Sign up to set email alerts
|

Mucins and Tight Junctions are Severely Altered in Necrotizing Enterocolitis Neonates

Abstract: Objective This study investigates the expression levels of mucin 1 (MUC1), MUC2, occludin, and zonula occludens-1 (ZO-1) in necrotizing enterocolitis (NEC). Study Design Intestinal specimens of surgical patients suffering from NEC (the NEC group) and intestinal specimens of patients with congenital intestinal atresia (the control group) were collected. Immunohistochemical changes in MUC1, MUC2, occludin, and ZO-1 were compared between the two groups. Results Our study showed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…The loss of tight junctions in NEC contributes to a leaky gut barrier (24,25) allowing bacterial translocation and increasing the risk of sepsis and death (18,26,27). Previous studies have found that ZO-1 mRNA expression is decreased in NEC tissue (24,25,28). We also demonstrated a decrease in the expression of the tight junction ZO-1 as well as its internalization by confocal microscopy and further demonstrated that the apparent paracellular permeability of the NEC-on-a-Chip system increases with time.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The loss of tight junctions in NEC contributes to a leaky gut barrier (24,25) allowing bacterial translocation and increasing the risk of sepsis and death (18,26,27). Previous studies have found that ZO-1 mRNA expression is decreased in NEC tissue (24,25,28). We also demonstrated a decrease in the expression of the tight junction ZO-1 as well as its internalization by confocal microscopy and further demonstrated that the apparent paracellular permeability of the NEC-on-a-Chip system increases with time.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to previous adult and pediatric Intestine-on-a-Chip models (16,17), the Neonatal-Intestine-on-a-Chip overcomes many limitations of traditional 2D and 3D intestinal cell culture techniques. The loss of tight junctions in NEC contributes to a leaky gut barrier (24,25) allowing bacterial translocation and increasing the risk of sepsis and death (18,26,27). Previous studies have found that ZO-1 mRNA expression is decreased in NEC tissue (24,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Muc2 deficient mice develop a more severe NEC pathology compared to those with normal mucin. [ 64 , 65 , 66 , 67 ]. Collectively, these data indicate a possible role for goblet cells in the development of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…During the early stages of NEC development, abnormal cell death and epithelial barrier disruption are necessary conditions for further development ( 11 , 15 , 16 ). Numerous studies have demonstrated that the intestinal barrier dysfunction observed in human NEC is characterized by the downregulation of mucins and TJ proteins, such as zonula occludens-1, occludin and claudin-4 ( 54 56 ). In this study, we found that the leakage of FITC-D into the circulation increased and the expression of claudin-1 and occludin decreased in NEC samples, suggesting severe barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%